Tracing belt and preparation method thereof
Through the trace belt structure, the cross-linked cured substance and particle design is used to solve the problems of large investment, high cost and short life of existing petroleum tracer, and low-cost and efficient long-term trace monitoring is achieved.
Patent Information
- Application Number
- CN202411680303.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-08-01
AI Technical Summary
The existing petroleum tracer has large investment, high cost and short service life, making it difficult to meet the needs of long-term monitoring.
The tracer belt structure is adopted, including a carrier and a sustained-release layer adhered thereto. The sustained-release layer consists of cross-linked cured substances, fluorescent microspheres and sustained-release materials. The carrier has mesh or pores. The fluorescent microspheres and sustained-release materials are hydrophilic or lipophilic. Combining particles and diluents, they are cured through cross-linking reactions to form a multi-layer sustained-release layer.
It reduces the amount of investment, reduces the cost, and significantly extends the service life, improves the sustained release effect and time of fluorescent microspheres, and enhances adhesion and stability.
Smart Images

Figure CN120412426A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the technical field of tracers. Specifically, it relates to a tracer tape and a preparation method thereof. Background Art
[0002] Fluorescent microspheres are formed by coating one or more fluorescent materials with a shell layer, which mainly serves to protect the fluorescent materials. The fluorescent materials mainly include: organic fluorescent dyes, quantum dots, metal oxides, etc. These fluorescent materials are easily affected by the environment, such as being easily degraded, easily photo-bleached, not resistant to high temperature / strong light irradiation, not resistant to water and oxygen, etc. Therefore, in the prior art, most fluorescent materials are coated with inorganic shell layers or organic polymer shell layers. The fluorescent materials are excited by light or electricity and emit fluorescence. By virtue of different types of fluorescent components and different fluorescence contents, multiple different emission bands (colors) can be formed, which has the function of encoding. Therefore, they are widely used in the fields of biological labeling, disease diagnosis, tracers, solid-phase chips, liquid-phase chips, immunochromatography, Raman scattering, etc.
[0003] When fluorescent microspheres are applied to petroleum tracers, usually sand grains such as quartz sand and ceramsite sand are used as the core, and a slow-release layer containing fluorescent microspheres, a slow-release material and resin is coated on the surface of the sand grains. The slow-release material slowly dissolves in the corresponding application environment, thereby slowly releasing the fluorescent microspheres wrapped by the slow-release material, which is usually called a coated sand tracer. By sampling and detecting the fluorescent microspheres, the position and distribution state of the tracer, the transportation state and flow state of petroleum, and whether different wells are connected can be judged, etc. The coated sand tracer is put in through the oilfield water injection port or injection port and monitored and sampled during the backflow period of the fracturing fluid. The input amount required is large and the cost is high; at the same time, the service life of the coated sand tracer is short, and the tracer needs to be put in again after a few hours.
[0004] In view of this, this application provides a tracer tape and a preparation method thereof. The tracer tape has a small input amount, low cost, and a long service life. Summary of the Invention
[0005] The purpose of this application is to provide a tracer tape and a preparation method thereof. The tracer tape has a small input amount, low cost, and a long service life.
[0006] In the first aspect of this application, a tracer tape is provided. The tracer tape includes: a carrier, and a slow-release layer adhesively fixed on the carrier. The slow-release layer includes: a crosslinked cured product, and fluorescent microspheres and a slow-release material distributed between the crosslinked cured products. The crosslinked cured product is formed by crosslinking and curing a resin.
[0007] In some embodiments, the carrier is used as a carrier for adhesively fixing the slow-release layer, and the carrier has a plurality of meshes or pores.
[0008] Further, the carrier includes at least one of a metal mesh, a scouring pad, an asbestos cloth, a nylon mesh, a polyester cloth, a polyimide mesh, or a polyurethane mesh.
[0009] In some embodiments, the slow-release layer includes a water-based slow-release layer or an oil-based slow-release layer, and the fluorescent microspheres and the slow-release material are both hydrophilic or lipophilic.
[0010] Further, when the slow-release layer is a water-based slow-release layer, the fluorescent microspheres and the slow-release material are hydrophilic; when the slow-release layer is an oil-based slow-release layer, the fluorescent microspheres and the slow-release material are lipophilic.
[0011] In some embodiments, the fluorescent microspheres include a fluorescent material and a shell layer coating the fluorescent material; polar groups or non-polar groups are self-borne or connected on the surface of the shell layer, making the fluorescent microspheres hydrophilic or lipophilic.
[0012] In some embodiments, the slow-release material can slowly dissolve in a polar solvent or a non-polar solvent.
[0013] Further, the hydrophilic slow-release materials include at least one of polyvinylpyrrolidone (K13, K30, K60, K90), polyvinyl alcohol, polysorbic acid, or polyoxyethylene polyoxypropylene copolymer.
[0014] Further, the lipophilic slow-release materials include at least one of petroleum resin and calcium stearate. The petroleum resin includes at least one of C5 petroleum resin and its derivatives or C9 petroleum resin and its derivatives.
[0015] In some embodiments, the resin includes at least one of phenolic resin, modified phenolic resin, or epoxy resin. The modified phenolic resin includes at least one of polyamide modified phenolic resin, dicyandiamide modified phenolic resin, epoxy modified phenolic resin, or polyvinyl acetal modified phenolic resin; the epoxy resin includes glycidyl ether type epoxy resin, and the glycidyl ether type epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, tetrabromobisphenol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol AD diglycidyl ether, aliphatic alcohol polyglycidyl ether, or linear phenolic polyglycidyl ether.
[0016] In some embodiments, the slow-release layer includes a crosslinked cured product and fluorescent microspheres, slow-release materials, and particles distributed between the crosslinked cured products.
[0017] Further, the particle size of the particles is greater than or equal to the particle size of the fluorescent microspheres, and the particle size of the particles is 1-4 times the particle size of the fluorescent microspheres.
[0018] Further, the particles include at least one of polystyrene microspheres, titanium dioxide microspheres, silicon dioxide microspheres, mesoporous silicon dioxide microspheres, carbon microspheres, polymethyl methacrylate microspheres, or magnetic microspheres.
[0019] Further, the particles can also be modified with hydrophilic ligands or lipophilic ligands, and the particles and the sustained-release material are both hydrophilic or lipophilic.
[0020] In some embodiments, the crosslinked cured product is formed by crosslinking and curing a resin and a diluent.
[0021] Further, the diluent can disperse the fluorescent microspheres and the sustained-release material, has epoxy groups, and its viscosity ≤ 1000 Pa·s (at 25 °C). Preferably, the viscosity of the diluent ≤ 100 Pa·s (at 25 °C).
[0022] Further, the fluorescent microspheres, the sustained-release material, and the diluent are all hydrophilic or lipophilic.
[0023] Further, the hydrophilic diluents include at least one of 1,4-butanediol diglycidyl ether, 2-ethylhexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, dimer acid diglycidyl ether, polyglycerol glycidyl ether, polyethylene glycol diglycidyl ether, or glycerol triglycidyl ether.
[0024] Further, the lipophilic diluents include at least one of epoxyethyl methyl neodecanoate, C8-C10 alkyl glycidyl ether, octyl glycidyl ether, butyl glycidyl ether, 2-phenyl glycidyl ether, nonylphenol glycidyl ether, or p-tert-butylphenyl 1-(2,3-epoxy)propyl ether.
[0025] In the second aspect of the present application, a method for preparing a tracer tape is provided, and the preparation method includes:
[0026] S1, mixing the fluorescent microspheres, the sustained-release material, the resin, and the curing agent evenly to form a mixed solution;
[0027] S2, coating the mixed solution onto a carrier, flattening it and then curing it to form a sustained-release layer adhesively fixed on the carrier, thereby obtaining a tracer tape.
[0028] In some embodiments, the mixed solution further includes particles. The fluorescent microspheres, the sustained-release material, the particles, the resin, and the curing agent are mixed evenly to form a mixed solution.
[0029] In some embodiments, the mixed solution further includes a diluent. The fluorescent microspheres, the sustained-release material, the diluent, the particles, the resin, and the curing agent are mixed evenly to form a mixed solution.
[0030] In some embodiments, in step S1, in the mixed solution, the mass ratio of the fluorescent microspheres is 1-9 wt%, the mass ratio of the sustained-release material is 8-40 wt%, the mass ratio of the diluent is 10-50 wt%, the mass ratio of the particles is 1-8 wt%, the mass ratio of the resin is 20-70 wt%, and the mass ratio of the curing agent is 13-35 wt%.
[0031] Preferably, in step S1, in the mixed solution, the mass ratio of the fluorescent microspheres is 2-7 wt%, the mass ratio of the sustained-release material is 10-35 wt%, the mass ratio of the diluent is 15-45 wt%, the mass ratio of the particles is 2-7 wt%, the mass ratio of the resin is 30-60 wt%, and the mass ratio of the curing agent is 15-30 wt%.
[0032] In some embodiments, at 10-80 °C, the fluorescent microspheres, the sustained-release material, the diluent, the particles, the resin, and the curing agent are mixed and stirred evenly at a speed of 200-900 rmp to form a mixed solution.
[0033] Preferably, at 20-40 °C, the fluorescent microspheres, the sustained-release material, the diluent, the particles, the resin, and the curing agent are mixed and stirred evenly at a speed of 300-600 rmp to form a mixed solution.
[0034] In some embodiments, in step S2, the mixed solution is coated on a carrier, rolled and leveled by a roller, left standing at 15-40 °C for 20-60 min, and then cured in an oven at 40-60 °C for 1.5-3 h to obtain a tracer tape.
[0035] In some embodiments, after the mixed solution coated is cured, the mixed solution can be coated again or multiple times and then cured to form a multi-layer sustained-release layer. The multi-layer sustained-release layer can further increase the loading capacity.
[0036] Furthermore, the mass ratios of the components in the mixed solution added each time are the same or different.
[0037] In some embodiments, the curing agent includes at least one of aliphatic amines and their modified products (such as EH451K, EH485, EH3895L, 593 curing agent), alicyclic amines and their modified products, low molecular weight polyamides, modified aromatic amines, polythiol type, or polyisocyanate type.
[0038] The tracer tape and its preparation method of the present application have at least the following advantages compared with the prior art:
[0039] (1) The tracer tape of the present application can be fixed inside the tracer sieve tube, enabling fixed-point input along with the tracer sieve tube, with a reduced input amount; and it can be self-cut to adapt to the sizes of different tracer sieve tubes. Moreover, the tracer tape adheres and fixes a large number of slow-release layers on the carrier, with a high loading amount of fluorescent microspheres thereon; the tracer tape is a material with multiple meshes or channels, which can increase the adhesion between the slow-release layer and the carrier, allowing more slow-release layers to be fixed. The slow-release effect of this slow-release layer is good, greatly increasing the service life of the tracer tape. For adhering the same mass of the slow-release layer, less amount of the carrier is required, and the carrier is inexpensive, further reducing the cost.
[0040] (2) The present application also adds particles to the slow-release layer to reduce the compactness of the network structure formed by resin cross-linking. When the slow-release material dissolves in a polar solvent or a non-polar solvent, the fluorescent microspheres and particles are released into the environmental solvent along with it. Since the particle size is 1 - 4 times that of the fluorescent microspheres, after the particles are released into the environmental solvent, large voids will be left, creating more slow-release channels for the internal fluorescent microspheres, thereby improving the slow-release effect and slow-release time of the fluorescent microspheres.
[0041] (3) The present application uses a diluent to replace conventional solvents such as ethanol to disperse / dissolve the fluorescent microspheres, slow-release materials, and particles, ensuring production safety. And this diluent has epoxy groups, which can undergo a cross-linking reaction with the resin under the action of a curing agent and cure. Therefore, there is no need for the step of high-temperature evaporation to remove the solvent, no volatile substances, and the synthesis step is simple; the synthesis at room temperature also makes the fluorescent microspheres not easily decomposed and stable.
[0042] (4) After the mixed solution coated on the carrier of the present application is cured, the mixed solution can be coated again or multiple times and then cured to form multiple slow-release layers, and the multiple slow-release layers can further increase the loading amount. Description of the Drawings
[0043] When read in conjunction with the following attached Figure 1 drawings, the above and other features of the content of the present application will be more fully described. It can be understood that these drawings only depict several embodiments of the content of the present application, and thus should not be considered as limiting the scope of the content of the present application. By using the drawings, the content of the present application will be described more clearly and in detail.
[0044] Figure 1 Fluorescence distribution diagram (660 channel) detected by a flow cytometer for the aqueous-phase tracer tape of Example 1 of the present application during the slow-release experiment, with samples taken at 1 h.
[0045] Figure 2 Fluorescence distribution diagram (585 channel) detected by a flow cytometer for the aqueous-phase tracer tape of Example 2 of the present application during the slow-release experiment, with samples taken at 1 h.
[0046] Figure 3 The sustained-release experiment of the aqueous tracer band of Example 3 of the present application was carried out, and the fluorescence distribution diagram (450 channels) of the sample taken 1 hour was detected by flow cytometry.
[0047] Figure 4 The sustained-release experiment was conducted on the aqueous tracer band of Example 4 of the present application, and the fluorescence distribution diagram (712 channels) of the sample taken 1 hour was detected by flow cytometry.
[0048] Figure 5 The sustained-release experiment of the oil-phase tracer band of Example 5 of the present application was carried out, and the fluorescence distribution diagram (525 channels) of the sample taken 1 hour was detected by flow cytometry.
[0049] Figure 6 The sustained-release experiment of the oil-phase tracer band of Example 6 of the present application was carried out, and the fluorescence distribution diagram (660 channels) of the sample taken 1 hour was detected by flow cytometry.
[0050] Figure 7 The sustained-release experiment of the oil-phase tracer band of Example 7 of the present application was carried out, and the fluorescence distribution diagram (585 channels) of the sample taken 1 hour was detected by flow cytometry.
[0051] Figure 8 The sustained-release experiment of the oil-phase tracer band of Example 8 of the present application was conducted, and the fluorescence distribution diagram (585 channels) of the sample taken 1 hour was detected by flow cytometry.
[0052] Figure 9 A sustained-release experiment was conducted on the aqueous coated sand tracer of Comparative Example 1 of the present application, and the fluorescence distribution diagram (660 channels) of the sample taken after 1 hour was detected by flow cytometry.
[0053] Figure 10 A sustained-release experiment was conducted on the oil-phase coated sand tracer of Comparative Example 2 of the present application, and the fluorescence distribution diagram (525 channels) of the sample taken 1 hour was detected by flow cytometry.
[0054] Figure 11 The sustained-release experiment of the aqueous tracer band of comparative example 3 of the present application was conducted, and the fluorescence distribution diagram (660 channels) of the sample taken 1 hour was detected by flow cytometry.
[0055] Figure 12 The sustained-release experiment of the oil-phase tracer band of comparative example 4 of the present application was conducted, and the fluorescence distribution diagram (525 channels) of the sample taken after 1 hour was detected by flow cytometry. DETAILED DESCRIPTION
[0056] The following examples are described to assist in understanding the present application, and the examples are not and should not be interpreted in any way as limiting the scope of protection of the present application.
[0057] Unless otherwise defined, all terms (including technical and scientific terms) used in this specification may be defined as commonly understood by one of ordinary skill in the art to which this disclosure pertains. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning that is consistent with their meaning in the context of this disclosure and the relevant art, and will not be interpreted in an idealized or overly formal sense unless clearly so defined herein.
[0058] As used herein, the term "at least one", when preceding or following a list of elements, modifies the entire list of elements and not individual elements of the list, and will not be construed to limit "one". "Or" means "and / or". The terms "comprising" and "including", when used in this specification, indicate the presence of the stated features, regions, wholes, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or their groups. Thus, the above wording will be understood to mean including the stated elements but not precluding any other elements. The term "and / or" includes any and all combinations of one or more of the associated listed items. The term "plurality" refers to two or more. The term "connected" refers to direct connection or indirect connection. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or an intermediate element may also be present. In contrast, when an element is referred to as being "directly on" another element, there is no intermediate element. To clearly illustrate the embodiments in the figures, some parts that are not actually relevant to the description may be omitted. The terms "first", "second", "third", etc. may be used herein to describe and distinguish different various elements, components, regions, layers, and / or parts, but these elements, components, regions, layers, and / or parts should not be limited by these terms.
[0059] In a first aspect of the present application, there is provided a tracer tape, the tracer tape comprising: a carrier, and a sustained-release layer adhesively fixed on the carrier, the sustained-release layer comprising: a crosslinked cured product, and fluorescent microspheres and a sustained-release material distributed between the crosslinked cured products, the crosslinked cured product being formed by curing a resin through a crosslinking reaction.
[0060] In some embodiments, the carrier is used as a carrier for adhesively fixing the sustained-release layer, and the carrier has a plurality of meshes or channels.
[0061] Furthermore, the carrier includes at least one of a metal mesh, a scouring pad, an asbestos cloth, a nylon mesh, a polyester cloth, a polyimide mesh, or a polyurethane mesh. In addition to these carriers listed above, any carrier that can adhere and fix the sustained-release layer is within the scope of protection of this application. The carrier having mesh holes or pores is only a preferred technical solution. The mesh holes or pores can only increase the adhesion between the sustained-release layer and the carrier.
[0062] The coated sand tracer is injected through the oil field water injection port or injection port, and the required injection amount is relatively large. The tracer tape can be fixed in the tracer screen tube, and can be injected at a fixed point along with the tracer screen tube, reducing the injection amount; and it can be cut by itself to adapt to the size of the tracer screen tube that is not needed. The tracer tape is a large amount of slow-release layer adhered and fixed on a carrier, and the loading amount of fluorescent microspheres thereon is high; while the coated sand tracer is a slow-release layer formed by fluorescent microspheres, slow-release materials and resins coated on the surface of quartz sand and ceramsite sand particles, and the loading amount of fluorescent microspheres thereon is relatively small. In addition, the tracer tape of the present application is a material with multiple meshes or pores, which can increase the adhesion between the slow-release layer and the carrier, and can fix more slow-release layers. To adhere the same quality of slow-release layer, the amount of quartz sand, ceramsite sand and other sand particles required is much larger, and the price of these sand particles is much higher than that of the carrier. The cost of the tracer tape of the present application is significantly lower than that of the coated sand tracer.
[0063] In some embodiments, the sustained-release layer comprises: an aqueous sustained-release layer and an oily sustained-release layer, and the fluorescent microspheres and the sustained-release material are both hydrophilic or lipophilic.
[0064] Furthermore, when the sustained-release layer is an aqueous sustained-release layer, the fluorescent microspheres and the sustained-release material are hydrophilic; when the sustained-release layer is an oily sustained-release layer, the fluorescent microspheres and the sustained-release material are lipophilic.
[0065] In some embodiments, the fluorescent microspheres include: a fluorescent material and a shell layer covering the fluorescent material; the shell layer has or is connected with polar groups or non-polar groups on its surface, making the fluorescent microspheres hydrophilic or lipophilic.
[0066] The fluorescent materials include at least one of fluorescent nanoparticles, fluorescent polymers, and organic fluorescent dyes. The fluorescent nanoparticles include at least one of quantum dots, metal oxide nanoparticles, nanorods, or nanosheets. The quantum dots include at least one of IIB-VIA group quantum dots, IIIA-VA group quantum dots, IVA-VIA group quantum dots, IVA group quantum dots, IB-IIIA-VIA group quantum dots, IB-IIB-IVA-VIA group quantum dots, VIII-VIA group quantum dots, perovskite quantum dots, and carbon quantum dots (carbon dots). These components are usually the core components of the quantum dots, and the quantum dots usually further include one or more shells (the outer shell is usually ZnS) that wrap the core. The metal oxides of the metal oxide nanoparticles include Zn, Cr, Co, Dy, Er, Eu, Fe, Gd, Pr, Nd, Ni, In, Pr, Sm, Tb, Tm, and combinations thereof. The fluorescent polymer has functional groups (such as fluorescein, etc.) capable of emitting fluorescence and monomers capable of polymerization in its structure. The monomers polymerize with each other or with other non-fluorescent monomers to prepare the fluorescent polymer. The organic fluorescent dyes include fluorescein (stilbenes, coumarins, fluorans, benzoxazoles, naphthalene diimides, thiophene dicarboxylic acid amides, polycyclic aromatic hydrocarbons, perylene tetracarboxylic diimides, etc.), aromatic polycyclic compounds, intramolecular charge transfer compounds, metal complex fluorescent materials, enzymes, and rare earth metal chelates.
[0067] More preferably, when the fluorescent microspheres are hydrophilic fluorescent microspheres, the surface of the shell layer of the fluorescent microspheres has polar groups by itself. The shell layer with polar groups by itself includes one of a silica shell layer, a titanium dioxide shell layer, a zirconium dioxide shell layer, a urea-formaldehyde shell layer, a urea-polyformaldehyde shell layer, a melamine-formaldehyde shell layer, a melamine-polyformaldehyde shell layer, a urea-melamine-formaldehyde, a urea-melamine-polyformaldehyde, a phenylmelamine formaldehyde shell layer, a phenylmelamine polyformaldehyde shell layer, a polar acrylic polymer shell layer, a polyurethane shell layer, a polyester shell layer, and a polyamide shell layer.
[0068] Further, when the fluorescent microspheres are lipophilic fluorescent microspheres, (usually) an oily ligand is modified on the surface of the shell layer. The oily ligands include at least one of polydimethylsiloxane, triethylchlorosilane, epoxyhexadecane, epoxy tetradecane, hexadecylamine, octadecylamine, chlorinated polystyrene, octadecyl maleic anhydride ester, hexadecyl maleic anhydride ester, tetradecyl maleic anhydride ester, polyethylene-alt-maleic anhydride copolymer, polypropylene-alt-maleic anhydride copolymer, polystyrene-alt-maleic anhydride copolymer, poly(maleic anhydride-1-octadecene), poly(maleic anhydride-1-hexadecene), poly(maleic anhydride-1-tetradecene), polyvinylpyrrolidone-hexadecene copolymer, polyoxyethylene-polyoxypropylene copolymer, long-chain fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, polyoxyethylene sorbitan laurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, sorbitan trioleate, sorbitan monostearate, sorbitan monooleate, sorbitan laurate.
[0069] In some embodiments, the sustained-release material can be slowly dissolved in a polar solvent or a non-polar solvent.
[0070] Further, the hydrophilic sustained-release materials include at least one of polyvinylpyrrolidone (K13, K30, K60, K90), polyvinyl alcohol, polysorbic acid, or polyoxyethylene-polyoxypropylene copolymer. In addition to these listed components, other sustained-release materials that can be slowly dissolved in polar solvents are also within the scope of protection of the present application.
[0071] Further, the lipophilic sustained-release materials include at least one of petroleum resin and calcium stearate. The petroleum resin includes at least one of C5 petroleum resin and its derivatives, or C9 petroleum resin and its derivatives. In addition to these listed components, other sustained-release materials that can be slowly dissolved in polar solvents are also within the scope of protection of the present application.
[0072] In some embodiments, the resin includes at least one of phenolic resin, modified phenolic resin, or epoxy resin. The modified phenolic resin includes at least one of polyamide-modified phenolic resin, dicyandiamide-modified phenolic resin, epoxy-modified phenolic resin, or polyvinyl acetal-modified phenolic resin; the epoxy resin includes glycidyl ether epoxy resin, and the glycidyl ether epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, tetrabromobisphenol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol AD diglycidyl ether, aliphatic alcohol polyglycidyl ether, or linear phenolic polyglycidyl ether.
[0073] In some embodiments, the sustained-release layer comprises: a crosslinked cured product, and fluorescent microspheres, a sustained-release material, and particles distributed among the crosslinked cured product.
[0074] Further, the particle size of the particles is greater than or equal to the particle size of the fluorescent microspheres, and the particle size of the particles is 1 to 4 times the particle size of the fluorescent microspheres, such as 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, or 4.0 times, but not limited to the listed values, and other unlisted values within the above range are equally applicable.
[0075] Further, the particles include at least one of polystyrene microspheres, titanium dioxide microspheres, silicon dioxide microspheres, mesoporous silicon dioxide microspheres, carbon microspheres, polymethyl methacrylate microspheres, or magnetic microspheres. In addition to these listed particles, other particulate substances that do not chemically react with the system components are also within the scope of protection of the present application.
[0076] Further, the particles can also be modified with hydrophilic ligands or lipophilic ligands, and the particles and the sustained-release material are both hydrophilic or lipophilic.
[0077] The crosslinked cured product has a network structure, which is insoluble in polar and non-polar solvents such as water and petroleum, and plays a role of a skeleton. The network structure of the crosslinked cured product can protect the fluorescent microspheres, the sustained-release material, and the particles (the fluorescent microspheres, the sustained-release material, and the particles are filled in the voids of the network structure), and at the same time prevent the fluorescent microspheres, the sustained-release material, and the particles from dissolving quickly, thereby achieving the effect of sustained release. When applied to a polar solvent such as water or a non-polar solvent environment such as petroleum, as the sustained-release material slowly dissolves in the environmental solvent, the fluorescent microspheres are gradually released into the environmental solvent.
[0078] On this basis, the present application further adds particles to the sustained-release layer, and the particle size of the particles is 1 to 4 times larger than that of the fluorescent microspheres. Since the network structure of the cured product formed by resin crosslinking is very dense, the fluorescent microspheres near the inner side of the sustained-release layer are not easily released. The present application adds particles to reduce the density of the network structure formed by resin crosslinking. When the sustained-release material dissolves in a polar solvent or a non-polar solvent, the fluorescent microspheres and the particles are released into the environmental solvent. Since the particle size of the particles is 1 to 4 times the particle size of the fluorescent microspheres, after the particles are released into the environmental solvent, large voids will be left, creating more sustained-release channels for the internal fluorescent microspheres, thereby improving the sustained-release effect and the sustained-release time of the fluorescent microspheres. When the particles are modified with ligands and have the same polarity as the sustained-release material, it is more conducive to the dispersion of the particles into the environmental solvent.
[0079] In some embodiments, the crosslinked cured product is formed by curing a resin and a diluent through a crosslinking reaction.
[0080] Furthermore, the diluent can disperse the fluorescent microspheres and the sustained-release material, has epoxy groups, and its viscosity ≤ 1000 Pa·s (at 25 °C), such as 10 Pa·s, 20 Pa·s, 30 Pa·s, 40 Pa·s, 50 Pa·s, 60 Pa·s, 70 Pa·s, 80 Pa·s, 90 Pa·s, 100 Pa·s, 200 Pa·s, 300 Pa·s, 400 Pa·s, 500 Pa·s, 600 Pa·s, 700 Pa·s, 800 Pa·s, 900 Pa·s, or 1000 Pa·s, but is not limited to the listed values, and other unlisted values within the above range are equally applicable. Preferably, the viscosity of the diluent ≤ 100 Pa·s (at 25 °C).
[0081] Furthermore, the fluorescent microspheres, the sustained-release material, and the diluent are all hydrophilic or lipophilic.
[0082] Furthermore, hydrophilic diluents include at least one of 1,4-butanediol diglycidyl ether, 2-ethylhexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, dimer acid diglycidyl ether, polyglycerol glycidyl ether, polyethylene glycol diglycidyl ether, or glycerol triglycidyl ether. In addition to these listed components, other hydrophilic diluents that can disperse fluorescent microspheres and sustained-release materials, have epoxy groups and meet the viscosity requirements are also within the protection scope of this application.
[0083] Furthermore, lipophilic diluents include at least one of epoxyethyl methyl neodecanoate, C8-C10 alkyl glycidyl ether, octyl glycidyl ether, butyl glycidyl ether, 2-phenyl glycidyl ether, nonylphenol glycidyl ether, or p-tert-butylphenyl 1-(2,3-epoxy)propyl ether. In addition to these listed components, other lipophilic diluents that can disperse fluorescent microspheres and sustained-release materials, have epoxy groups and meet the viscosity requirements are also within the protection scope of this application.
[0084] This application uses a diluent to replace conventional solvents such as ethanol to disperse / dissolve fluorescent microspheres, sustained-release materials, and particles (for production safety). And this diluent has epoxy groups and can undergo a crosslinking reaction with the resin under the action of a curing agent to cure. Therefore, there is no need to perform a step of high-temperature evaporation to remove the solvent, there are no volatile substances (such as formaldehyde released by MF microspheres), the synthesis step is simple (short production time); synthesis at room temperature also makes the fluorescent microspheres not easily decomposed and stable (less adverse effects on the fluorescent microspheres).
[0085] In a second aspect of the present application, a method for preparing a tracer tape is provided, and the preparation method includes:
[0086] S1, mixing fluorescent microspheres, a sustained-release material, a resin, and a curing agent uniformly to form a mixed solution;
[0087] S2, coating the mixed solution onto a carrier, flattening it, and then curing it to form a sustained-release layer adhesively fixed to the carrier, thereby obtaining the tracer tape.
[0088] In some embodiments, the mixed solution further includes: particles. The fluorescent microspheres, the sustained-release material, the particles, the resin, and the curing agent are mixed uniformly to form the mixed solution.
[0089] In some embodiments, the mixed solution further includes: a diluent. The fluorescent microspheres, the sustained-release material, the diluent, the particles, the resin, and the curing agent are mixed uniformly to form the mixed solution.
[0090] In some embodiments, in step S1, in the mixed solution, the mass ratio of the fluorescent microspheres is 1-9 wt%, such as 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, or 9 wt%, but not limited to the listed values, and other unlisted values within the above range are equally applicable; the mass ratio of the sustained-release material is 8-40 wt%, such as 8 wt%, 10 wt%, 12 wt%, 14 wt%, 17 wt%, 20 wt%, 24 wt%, 28 wt%, 30 wt%, 32 wt%, 34 wt%, 36 wt%, 38 wt%, or 40 wt%, but not limited to the listed values, and other unlisted values within the above range are equally applicable; the mass ratio of the diluent is 10-50 wt%, such as 10 wt%, 12 wt%, 14 wt%, 17 wt%, 20 wt%, 24 wt%, 28 wt%, 30 wt%, 32 wt%, 34 wt%, 36 wt%, 38 wt%, 40 wt%, 42 wt%, 44 wt%, 46 wt%, 48 wt%, 50 wt%, but not limited to the listed values, and other unlisted values within the above range are equally applicable; the mass ratio of the particles is 1-8 wt%, such as 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, or 8 wt%, but not limited to the listed values, and other unlisted values within the above range are equally applicable; the mass ratio of the resin is 20-70 wt%, such as 20 wt%, 24 wt%, 28 wt%, 30 wt%, 32 wt%, 34 wt%, 36 wt%, 38 wt%, 40 wt%, 42 wt%, 44 wt%, 46 wt%, 48 wt%, 50 wt%, 50 wt%, 54 wt%, 58 wt%, 60 wt%, 62 wt%, 64 wt%, 66 wt%, 68 wt%, or 70 wt%, but not limited to the listed values, and other unlisted values within the above range are equally applicable; the mass ratio of the curing agent is 13-35 wt%, such as 13 wt%, 14 wt%, 17 wt%, 20 wt%, 24 wt%, 28 wt%, 30 wt%, 32 wt%, 34 wt%, or 35 wt%, but not limited to the listed values, and other unlisted values within the above range are equally applicable.
[0091] Preferably, in step S1, in the mixed solution, the mass ratio of the fluorescent microspheres is 2-7 wt%, the mass ratio of the sustained-release material is 10-35 wt%, the mass ratio of the diluent is 15-45 wt%, the mass ratio of the particles is 2-7 wt%, the mass ratio of the resin is 30-60 wt%, and the mass ratio of the curing agent is 15-30 wt%.
[0092] In some embodiments, at 10 - 80 °C, such as 10 °C, 20 °C, 30 °C, 40 °C, 50 °C, 60 °C, 70 °C, or 80 °C, but not limited to the listed values, other unlisted values within the above range are equally applicable. Mix the fluorescent microspheres, sustained-release material, diluent, particles, resin, and curing agent, and stir and mix evenly at a speed of 200 - 900 rmp, such as 200 rmp, 300 rmp, 400 rmp, 500 rmp, 600 rmp, 700 rmp, 800 rmp, or 900 rmp, but not limited to the listed values, and other unlisted values within the above range are equally applicable, to form a mixed solution.
[0093] Preferably, at 20 - 40 °C, mix the fluorescent microspheres, sustained-release material, diluent, particles, resin, and curing agent, and stir and mix evenly at a speed of 300 - 600 rmp to form a mixed solution.
[0094] In some embodiments, in step S2, coat the mixed solution onto a carrier, and after rolling and leveling with a roller, let it stand at 15 - 40 °C (such as 15 °C, 17 °C, 20 °C, 23 °C, 25 °C, 28 °C, 30 °C, 32 °C, 34 °C, 36 °C, 38 °C, or 40 °C, but not limited to the listed values, and other unlisted values within the above range are equally applicable) for 20 - 60 min, such as 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, but not limited to the listed values, and other unlisted values within the above range are equally applicable. Then place it in an oven at 40 - 60 °C (such as 40 °C, 42 °C, 44 °C, 46 °C, 48 °C, 50 °C, 52 °C, 54 °C, 56 °C, 58 °C, or 60 °C, but not limited to the listed values, and other unlisted values within the above range are equally applicable) for curing for 1.5 - 3 h, such as 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h, or 3.0 h, but not limited to the listed values, and other unlisted values within the above range are equally applicable, to obtain a tracer strip.
[0095] In some embodiments, after the mixed solution coated is cured, the mixed solution can be coated again or multiple times and then cured to form a multi-layer sustained-release layer. The multi-layer sustained-release layer can further increase the loading capacity.
[0096] Furthermore, the mass ratios of the components in the mixed solution added each time are the same or different.
[0097] In some embodiments, the curing agent includes at least one of aliphatic amines and their modified products (such as EH451K, EH485, EH3895L, 593 curing agent), alicyclic amines and their modified products, low molecular weight polyamides, modified aromatic amines, polythiol type, or polyisocyanate type.
[0098] The present invention will be further described in detail below in conjunction with specific examples and comparative examples, but the present invention is not limited to the following examples. The implementation conditions adopted in the examples can be further adjusted according to different requirements of specific use, and the conditions not specified are conventional conditions in this industry.
[0099] Example 1:
[0100] Take 12 g of fluorescent microspheres (fluorescent material is Nile red, shell layer is melamine - paraformaldehyde, particle size 3.7 μm), and successively add 60 g of ethylene glycol diglycidyl ether and 68 g of polyvinylpyrrolidone (PVP - K30). Stir at room temperature of 25 °C and a speed of 500 rmp for 10 min; then add 12 g of titanium dioxide microspheres (particle size 6 μm), 150 g of bisphenol A epoxy resin, and 60 g of modified aliphatic amine (curing agent EH - 451K), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0101] Uniformly coat the mixed solution on the surface of a 200 - mesh scouring pad, and after rolling and leveling with a roller, let it stand at room temperature of 25 °C for 30 min, and then place it in an oven at 45 °C for curing for 2 h; a water - phase tracer tape is obtained.
[0102] Example 2:
[0103] Take 12 g of fluorescent microspheres (fluorescent material is Rhodamine B, shell layer is melamine - formaldehyde, particle size 2.2 μm), and successively add 62 g of 1,4 - butanediol diglycidyl ether and 70 g of polyvinyl alcohol. Stir at room temperature of 25 °C and a speed of 500 rmp for 10 min; then add 12 g of polystyrene microspheres (particle size 4.2 μm), 160 g of phenolic resin, and 60 g of modified aliphatic amine (curing agent EH - 485), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0104] Uniformly coat the mixed solution on the surface of a 150 - mesh scouring pad, and after rolling and leveling with a roller, let it stand at room temperature of 25 °C for 30 min, and then place it in an oven at 45 °C for curing for 2 h to obtain a water - phase tracer tape.
[0105] Example 3:
[0106] Take 12 g of fluorescent microspheres (the fluorescent material is coumarin, the shell layer is a silica shell layer, and the particle size is 1.8 μm), and successively add 65 g of dipropylene glycol diglycidyl ether and 65 g of polyvinylpyrrolidone (PVP-K60). Stir at 25 °C at a rotation speed of 500 rmp for 10 min; then add 12 g of silica microspheres (particle size 3 μm), 120 g of epoxy-modified phenolic resin, and 48 g of modified aliphatic amine (curing agent EH-593), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0107] Evenly coat the mixed solution on the surface of a 200-mesh scouring pad, and use a roller to roll and level it. Then, let it stand at room temperature (25 °C) for 30 min, and then place it in an oven at 45 °C for curing for 2 h; repeat the above coating and curing process once to obtain a high-loading multilayer aqueous phase tracer tape.
[0108] Example 4:
[0109] Take 12 g of fluorescent microspheres (the fluorescent material is near-infrared cyanine CY5.5, the shell layer is urea-polyformaldehyde, and the particle size is 3.7 μm), and successively add 62 g of glycerol triglycidyl ether and 70 g of polyoxyethylene polyoxypropylene copolymer. Stir at 25 °C at a rotation speed of 500 rmp for 10 min; then add 12 g of polymethyl methacrylate microspheres (particle size 6 μm), 160 g of bisphenol AD diglycidyl ether, and 60 g of modified aliphatic amine (curing agent EH-3895L), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0110] Evenly coat the mixed solution on the surface of a 150-mesh scouring pad, and use a roller to roll and level it. Then, let it stand at room temperature (25 °C) for 30 min, and then place it in an oven at 45 °C for curing for 2 h; repeat the above coating and curing process twice to obtain a high-loading multilayer aqueous phase tracer tape.
[0111] Example 5:
[0112] Take 12 g of fluorescent microspheres (the fluorescent material is sodium fluorescein, the shell layer is urea-polyformaldehyde, the oily ligand is poly(maleic anhydride-alt-1-octadecene) and polyoxyethylene-polyoxypropylene copolymer, and the particle size is 3.7 μm), and successively add 60 g of butyl glycidyl ether and 68 g of C9 petroleum resin. Stir at 25 °C at a rotation speed of 500 rmp for 10 min; then add 12 g of titanium dioxide microspheres (particle size 6 μm), 130 g of bisphenol A epoxy resin, and 60 g of modified aliphatic amine (curing agent EH-451K), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0113] Evenly coat the mixed solution on the surface of a 200-mesh scouring pad, and use a roller to roll and level it. Then, let it stand at room temperature (25 °C) for 30 min, and then place it in an oven at 45 °C for curing for 2 h; obtain an oil phase tracer tape.
[0114] Example 6:
[0115] Take 12 g of fluorescent microspheres (the fluorescent material is Nile red, the shell layer is polystyrene, the oily ligand is poly(maleic anhydride octadecene) and hydroxyl-terminated polydimethylsiloxane, with a particle size of 4.0 μm), and successively add 62 g of ethylene oxide methyl neodecanoate and 70 g of C5 petroleum resin. Stir at room temperature of 25°C and a rotation speed of 500 rmp for 10 min; then add 12 g of polystyrene microspheres (particle size 4 μm), 160 g of phenolic resin, and 60 g of modified aliphatic amine (curing agent EH-451K), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0116] Evenly coat the mixed solution on the surface of a 150-mesh scouring pad, and after rolling and leveling with a roller, let it stand at room temperature of 25°C for 30 min, and then place it in an oven at 45°C for curing for 2 h to obtain a high-loading multilayer oil-phase tracer tape.
[0117] Example 7:
[0118] Take 12 g of fluorescent microspheres (the fluorescent material is Rhodamine B, the shell layer is polyacrylic acid, the oily ligand is methyl methacrylate-styrene copolymer and triethylchlorosilane, with a particle size of 2.8 μm), and successively add 65 g of nonylphenol glycidyl ether and 65 g of C9 petroleum resin. Stir at room temperature of 25°C and a rotation speed of 500 rmp for 10 min; then add 12 g of silica microspheres (particle size 5 μm), 120 g of epoxy-modified phenolic resin, and 60 g of modified aliphatic amine (curing agent EH-485), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0119] Evenly coat the mixed solution on the surface of a 200-mesh scouring pad, and after rolling and leveling with a roller, let it stand at room temperature of 25°C for 30 min, and then place it in an oven at 45°C for curing for 2 h; repeat the above coating and curing process once to obtain a high-loading multilayer oil-phase tracer tape.
[0120] Example 8:
[0121] Take 12 g of fluorescent microspheres (the fluorescent material is Rhodamine B, the shell layer is melamine-formaldehyde, the oily ligand is poly(maleic anhydride-1-octadecene) and polyethylene oxide-polypropylene oxide copolymer, with a particle size of 3.7 μm), and successively add 62 g of butyl glycidyl ether and 70 g of C9 petroleum resin. Stir at room temperature of 25°C and a rotation speed of 500 rmp for 10 min; then add 12 g of polymethyl methacrylate microspheres (particle size 6 μm), 160 g of bisphenol AD diglycidyl ether, and 60 g of modified aliphatic amine (curing agent EH-593), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0122] The mixture was evenly coated on the surface of a 150-mesh scouring pad, and after being rolled and leveled with a roller, it was left standing at room temperature of 25 °C for 30 min, and then placed in an oven at 45 °C for curing for 2 h; the above coating and curing process was repeated twice to obtain a high-loading multi-layer oil-phase tracer tape.
[0123] Comparative Example 1:
[0124] Take 25 g of fluorescent microspheres (the fluorescent material is Nile red, the shell layer is melamine-polyformaldehyde, and the particle size is 3.7 μm), add 120 g of polyvinylpyrrolidone (PVP-K30) and 330 g of ethyl acetate and mix evenly (stir at 400 rmp for 15 min at room temperature of 25 °C); then add 620 g of bisphenol A epoxy resin and continue to stir for 20 min under the same conditions to obtain the first mixed solution.
[0125] Mix 25 kg of quartz sand with 14 kg of ethanol evenly in a reaction kettle (stir at 30 HZ for 20 min), and raise the temperature in the reaction kettle to 70 °C. Immediately after reaching 70 °C, put the first mixed solution into the reaction kettle and mix evenly (stir at 30 HZ for 20 min), and then raise the temperature to 80 °C to remove the solvent; after all the solvent is removed, add 260 g of modified aliphatic amine (curing agent EH-451K) and react for 2 h. After cooling, discharge the material to obtain an aqueous phase coated sand tracer.
[0126] Comparative Example 2:
[0127] Take 25 g of oily fluorescent microspheres (the fluorescent material is sodium fluorescein, the shell layer is urea-polyformaldehyde, the oily ligand is poly(maleic anhydride-1-octadecene) and poly(oxyethylene-oxypropylene) copolymer, and the particle size is 3.7 μm), add 90 g of C9 petroleum resin and 300 g of ethyl acetate and mix evenly (stir at 500 rmp for 15 min at room temperature of 25 °C); then add 600 g of bisphenol A epoxy resin and continue to stir for 20 min under the same conditions to obtain the first mixed solution.
[0128] Mix 25 kg of quartz sand with 23 kg of ethanol evenly in a reaction kettle (stir at 30 HZ for 20 min), and raise the temperature in the reaction kettle to 70 °C. Immediately after reaching 70 °C, put the first mixed solution into the reaction kettle and mix evenly (stir at 30 HZ for 20 min), and then raise the temperature to 80 °C to remove the solvent; after all the solvent is removed, add 250 g of modified aliphatic amine (curing agent EH-451K) and react for 3 h. After cooling, discharge the material to obtain an oil-phase coated sand tracer.
[0129] Comparative Example 3:
[0130] Take 12 g of fluorescent microspheres (the fluorescent material is Nile red, the shell layer is melamine - paraformaldehyde, and the particle size is 3.7 μm), and successively add 600 g of ethanol and 68 g of polyvinylpyrrolidone (PVP - K30). Stir at room temperature of 25 °C and a rotation speed of 500 rmp for 10 min; then add 150 g of bisphenol A epoxy resin and 60 g of modified aliphatic amine (curing agent EH - 451K), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0131] Uniformly coat the mixed solution on the surface of a 200 - mesh scouring pad, and after rolling and leveling with a roller, let it stand at room temperature of 25 °C for 30 min, and then place it in an oven at 45 °C for curing for 2 h; then place it in an oven at 80 °C for 30 min to remove the residual ethanol; obtain an aqueous - phase tracer tape.
[0132] Comparative Example 4:
[0133] Take 12 g of fluorescent microspheres (the fluorescent material is sodium fluorescein, the shell layer is urea - paraformaldehyde, the oily ligand is poly (maleic anhydride - 1 - octadecene) and polyoxyethylene - polyoxypropylene copolymer, and the particle size is 3.7 μm), and successively add 600 g of ethanol and 68 g of C9 petroleum resin. Stir at room temperature of 25 °C and a rotation speed of 500 rmp for 10 min; then add 130 g of bisphenol A epoxy resin and 60 g of modified aliphatic amine (curing agent EH - 451K), and continue to stir for 20 min under the same conditions to obtain a mixed solution.
[0134] Uniformly coat the mixed solution on the surface of a 200 - mesh scouring pad, and after rolling and leveling with a roller, let it stand at room temperature of 25 °C for 30 min, and then place it in an oven at 45 °C for curing for 2 h; then place it in an oven at 80 °C for 30 min to remove the residual ethanol; obtain an oil - phase tracer tape.
[0135] Take 1 g of the aqueous - phase tracer tape / coated - sand tracer of Examples 1 - 4 and Comparative Examples 1 and 3 respectively and place them in glass bottles, and then add 50 g of deionized water. Take 1 g of the oil - phase tracer tape / coated - sand tracer of Examples 5 - 8 and Comparative Examples 2 and 4 respectively and place them in glass bottles, and then add 50 g of n - octane. Then place the glass bottles into an oil - bath pot, turn on the peristaltic pump (the pump speed is 120 rmp), and the temperature in the oil - bath pot is 90 °C for oscillating accelerated aging and slow release. After a certain time, sample, each time take 0.3 ml of the solution, and replace the fresh deionized water or n - octane after each sampling. For the sampled samples, use a flow cytometer to detect the number of fluorescent microspheres released into the solvent in the samples (the injection volume of the flow cytometer is: 10 μl / min * 20 s), and the counting results are shown in Table 1. Among them, for Examples 1 - 8 and Comparative Examples 1 - 4, at the first detection time (1 h), the fluorescence distribution maps were also detected by a flow cytometer, respectively successively as Figures 1-12 shown.
[0136] Table 1: Sustained-release data of Examples 1-8 and Comparative Examples 1-4.
[0137]
[0138] As can be seen from Table 1, for the aqueous-phase tracer bands of Examples 1-4 and the oil-phase tracer bands of Examples 5-8 of the present application, the loading amount of the fluorescent microspheres is high, and the sustained-release effect is relatively gentle, and it can be applied to groundwater or oilfield tracing for a long time. Comparative Example 1 is an aqueous-phase coated sand tracer. Compared with the aqueous-phase tracer band, the loading amount of its fluorescent microspheres is significantly lower, and it is all released within a few hours, with a short service life. Comparative Example 2 is an oil-phase coated sand tracer. Compared with the oil-phase tracer band, the loading amount of its fluorescent microspheres is significantly lower, and the number of fluorescent microspheres released into the environmental solvent is small, which is not conducive to actual detection. There is no obvious difference in the loading amount of the fluorescent microspheres between Comparative Example 3 and Examples 1-4, and between Comparative Example 4 and Examples 5-8, and there is also no obvious difference in the sustained-release effect within 2 days. However, starting from the 3rd day, the number of fluorescent microspheres released is significantly less than that of Examples 1-4 or Examples 5-8.
[0139] Although the present application has disclosed multiple aspects and embodiments, other aspects and embodiments will be obvious to those skilled in the art. Without departing from the concept of the present application, several modifications and improvements can still be made, and these all belong to the protection scope of the present application. The multiple aspects and embodiments disclosed in the present application are only for illustrative purposes and are not intended to limit the present application. The actual protection scope of the present application is subject to the claims.
Claims
1. A tracer tape, characterized in that, The tracer tape includes: a carrier, and a slow-release layer adhesively fixed to the carrier. The slow-release layer includes: a crosslinked cured product, and fluorescent microspheres and a slow-release material distributed among the crosslinked cured products. The crosslinked cured product is formed by curing a resin through a crosslinking reaction.
2. The tracer tape according to claim 1, characterized in that, The carrier is used as a carrier for adhesively fixing the slow-release layer, and the carrier has a plurality of meshes or pores. Preferably, the carrier includes at least one of: a metal mesh, a scouring pad, an asbestos cloth, a nylon mesh, a polyester cloth, a polyimide mesh, or a polyurethane mesh.
3. The tracer tape according to claim 1, characterized in that, It includes one or more features selected from the following groups: (1) The slow-release layer includes one of: an aqueous slow-release layer, an oil-based slow-release layer. The fluorescent microspheres and the slow-release material are both hydrophilic or lipophilic. (2) The fluorescent microspheres include: a fluorescent material, and a shell layer coating the fluorescent material; polar groups or non-polar groups are self-borne or connected on the surface of the shell layer, so that the fluorescent microspheres have hydrophilicity or lipophilicity. (3) The slow-release material can slowly dissolve in a polar solvent or a non-polar solvent. (4) The resin includes at least one of: a phenolic resin, a modified phenolic resin, or an epoxy resin.
4. The tracer tape according to claim 1, characterized in that, The slow-release layer includes: a crosslinked cured product, and fluorescent microspheres, a slow-release material, and particles distributed among the crosslinked cured products.
5. The tracer tape according to claim 4, characterized in that, The particle size of the particles is greater than or equal to the particle size of the fluorescent microspheres, and the particle size of the particles is 1-4 times the particle size of the fluorescent microspheres. Preferably, the particles include at least one of: polystyrene microspheres, titanium dioxide microspheres, silicon dioxide microspheres, mesoporous silicon dioxide microspheres, carbon microspheres, poly(methyl methacrylate) microspheres, or magnetic microspheres; the particles can also be modified with hydrophilic ligands or lipophilic ligands, and the particles and the slow-release material are both hydrophilic or lipophilic.
6. The tracer tape according to claim 1, wherein The crosslinked cured product is formed by curing a resin and a diluent through a crosslinking reaction. Preferably, the diluent can disperse the fluorescent microspheres and the slow-release material, has an epoxy group, and its viscosity ≤ 1000 Pa·s. Preferably, the fluorescent microspheres, the slow-release material, and the diluent are all hydrophilic or lipophilic.
7. A method for preparing a tracer tape, characterized in that, The preparation method includes: S1, uniformly mixing fluorescent microspheres, a slow-release material, a resin, and a curing agent to form a mixed solution. S2, coating the mixed solution onto the carrier, flattening it and then curing it to form a slow-release layer adhesively fixed to the carrier, thereby obtaining the tracer tape.
8. The preparation method of the tracer tape according to claim 7, characterized in that, The mixed solution further includes: particles; the mixed solution further includes: a diluent.
9. The preparation method of the tracer tape according to claim 8, wherein, In step S1, in the mixed solution, the mass ratio of the fluorescent microspheres is 1-9 wt%, the mass ratio of the slow-release material is 8-40 wt%, the mass ratio of the diluent is 10-50 wt%, the mass ratio of the particles is 1-8 wt%, the mass ratio of the resin is 20-70 wt%, and the mass ratio of the curing agent is 13-35 wt%.
10. The preparation method of the tracer tape according to any one of claims 7-9, characterized in that, After the coated mixed solution is cured, the mixed solution can be coated again or multiple times and then cured to form a multi-layer slow-release layer.